READINESS OF INTERPROFESSIONAL EDUCATION IN COMMUNITY MEDICINE: MEDICAL AND DENTISTRY STUDENTS - Chamim Faizin (Journal Medical Universitas muhammadiyah Makassar, 2023)
Abstract The condition of public health is a reflection of the level of complexity of health problems. Many health care systems have innovated but failed in the practice of collaboration, teamwork, and communication. Family-based care will ease the workload of doctors and improve the level of health for patients in the community. Interprofessional education program was designed to increase of collaborative practice and teamwork among health team. This review aims to analyze the readiness of interprofessional education (IPE) in medical and dentistry students in collaborative field practice community medicine with a family approach. Quantitative methods using cross sectional with the readiness interprofessional learning scale (RIPLS). Total sampling with 142 medical students and 43 dental students carried out collaborative practice on 16 families to find priority health problems and carry out preventive interventions. The average readiness of interprofessional education descriptively for students is 65.36% (range 50%-76%). 100% student ready for interprofessional education. No difference among medical and dentistry student in readiness of interprofessional education with p value 0,810 (0,05). That all student ready to interprofessional education community medicine with family approach. Key words : readiness, interprofessional education, community medicine, medical students, dental students